Digital tax transformation and compliance behaviour: The moderating role of social norms in Indonesian corporate tax system - Lumbantobing, Sabar Pardamean; Adwimurti, Yudhistira (Jurnal Akuntansi dan Auditing Indonesia, 2026)
This study examines whether digital tax transformation improves corporate tax compliance and whether social norms condition that effect. The Indonesian setting is relevant because firms have faced a broader digitalisation of tax administration alongside mandatory e-invoicing under PER-03/PJ/2022. Building on the Slippery Slope Framework and the literature on digital tax administration, we analyse survey and archival data from 566 Indonesian corporations for the 2020-2024 period. The study applies a two-stage procedure: survey-based constructs are first validated through factor analysis, and the hypotheses are then tested using hierarchical regression with interaction terms. The results show that trust in tax authorities, authority power, and e-invoicing implementation are positively associated with corporate tax compliance. More importantly, social norms strengthen each relationship, indicating that formal enforcement and digital systems operate more effectively when firms perceive compliance as the expected conduct among relevant peers. The enhanced e-invoicing index, which combines technical adoption, data quality, system integration, and regulatory adherence, explains more variation than a simple adoption measure. The findings contribute to tax compliance research by showing that digital reform should be assessed not only as a technological intervention but also as an institutional process embedded in social expectations.